Pengembangan Media Pembelajaran Augmented Reality Materi Kerajaan Hindu Budha Untuk Meningkatkan Berpikir Kritis Siswa Kelas IV SD - Afifah, Awayna Faza; Zainuddin, Almuntaqo (Universitas Nahdlatul Ulama Blitar, 2025)
This study aims to provide changes to the Instagram Augmented Reality filter teaching media on Hindu Buddhist Kingdom material and determine student responses with a focus on improving the critical reasoning of class IV students at SD Muhammadiyah 1 Surakarta. This research uses the Research and Development (R&D) method with the ADDIE model. This media feasibility test is based on media experts and material experts through media and material expert validation sheets. Student responses with questionnaires and pre-test and post-test work to determine changes in students' critical reasoning. The results of the research stated that the Hindu Buddhist Kingdom learning media based on Instagram AR filters obtained a percentage score of 86.25% by media experts, 84.61% by material experts, and 98.84% by practitioners as material experts. Based on the Likert scale, the percentage scores are both included in the